Pancasila and Civic Education Olympics in East Java Province: Prototype to Increase Nationalism & Political Participation of Youths - Wafa, Ali (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Political uncertainty in Indonesia will threaten domestic political stability and participation. The failure of government performance and high corruption practices are reasons for public despair. Departing from this reality, we thought of an alternative to reduce this despair through civic education in the form of a competition. This competition will be an annual agenda to prepare talented youth in East Java Province, with strong leadership and academic potential. Using the Participatory Learning and Action approach, this service took place over 5 months (November 2022-March 2023). The final results showed that; all participants showed their best performance in each session, to interpret the 4 pillars of nationality (Pancasila, 1945 Constitution, NKRI, and Bhinneka Tunggal Ika). Participants were also able to interpret the nation's problems on the issues of radicalism, nationalism, poverty, and youth through creative ideas. 12 participants won the main award and 10 participants won the best presenter award. All participants also attended a nationality camp, which was supported by the National Unity and Political Agency of Jember Regency.